In vitro activity of anti-rheumatic drugs on release of pro-inflammatory cytokines from oral cells in interaction with microorganisms - Stähli, Alexandra; Scherler, Carina; Zappalà, Graziano; Sculean, Anton; Eick, Sigrun (Frontiers in Oral Health, 2022)
Periodontitis patients suffering concomitantly from rheumatoid arthritis (RA) often present with less inflamed periodontal tissues due to the ongoing anti-rheumatic therapy. This in-vitro study was aimed to analyze whether anti-inflammatory drugs used in the therapy of RA can modulate the release of IL-8 and IL-1β by professional and non-professional immune cells stimulated with microorganisms. Periodontal ligament (PDL) fibroblasts, monocytic MONO-MAC-6-cells and gingival keratinocytes were exposed to ibuprofen, prednisolone, and methotrexate with and without lysates of Fusobacterium nucleatum or Candida albicans. Supernatants were obtained and the levels of interleukin(IL)-8 and IL-1β (only MONO-MAC-6) were quantified. Addition of F. nucleatum lysate resulted in the strongest release of proinflammatory cytokines by PDL fibroblast and MONO-MAC-6 cells, while the modification by the tested anti-rheumatic drugs was only minor. After stimulation of the MONO-MAC-cells with F. nucleatum, prednisolone increased the release of IL-8, whereas methotrexate decreased the level. Anti-inflammatory drugs increased the adherence of C. albicans to epithelial cells. In patients with RA, the reduction of the microbial load in subgingival biofilm (biofilm removal) is of major importance, however, the intake of inflammatory drugs may interfere with the inflammatory response.